PROSES PENGAKUAN DAN PENGUKURAN ASET TAK BERWUJUD DATA DAN INFORMASI GEOSPASIAL: KELEMAHAN DAN KENDALA - Rosdiana, Nur Sumi Mina; Viska Anggraita (Jurnal Akuntansi Trisakti, 2024)
The research was conducted to analyze the weaknesses and obstacles in the recognition and measurement process of intangible assets of geospatial data and information at the Geospatial Information Agency (BIG). These intangible assets are generated from the implementation of basic geospatial data and information activities as the main business process and thus dominate the balance sheet. In its recognition and measurement, BIG implements internal guidelines that refer to government accounting standards. Recognition is through meeting the definition and criteria of intangible assets and measurement is through identifying costs that can be capitalized into acquisition costs, related to budgeting, budget execution, and reporting. Problems occurred in the implementation of the guidelines, such as in determining the costs that can be capitalized and the number of transaction corrections that hamper the preparation of financial statements. The research was conducted through document analysis, observation, and interviews. Based on the research results, weaknesses were found in budgeting, budget execution, and reporting. Constraints based on Edwards' (1980) policy implementation model were identified in the factors of communication, resources, disposition, and bureaucratic structure and interacted simultaneously. These weaknesses and constraints have the potential to cause understated and overstated intangible assets that require value corrections and adjustment journals presented in the financial statements. This study provides recommendations to overcome the weaknesses and obstacles in the implementation of the guidelines to mitigate the number of transaction corrections that occur in the preparation of financial statements.